Neutrality of Money in Iran’s Service Sector - Banafsheh Najafi; Nader Hakimipour; hojjat akbarian (پژوهشهای اقتصادی, 2018)
Service sector has been changed qualitatively and quantitatively in Iran over the time. Its share in sectoral value-added, GDP, employment and absorption of the resources has been increasing dramatically in recent years. In this paper, neutrality and super neutrality of money in service sector are tested using data on services’ value added, the monetary base, liquidity and money supply by using Fisher-Seater methodology during 1973-2015. In order to determine the degree of the stationary, various unit root tests are used. Since ADF, KPSS and PP unit root tests do not consider the structural breaks; this paper applies Zivot and Andrews unit root test. The results show that, firstly, Zivot & Andrews method is relevant to test for unit root because of structural breaks in variables. Secondly, money in the services sector is not neutral; and permanent changes in monetary variables affect real production. This leads policymakers to make expansionary monetary policies and consider the relevant costs incurred by people.